The Spanish universities in Twitter: Messages, contents and publics - Gómez Calderón, Bernardo J.; Paniagua Rojano, Francisco Javier (Historia y Comunicación Social, 2014)
The use of Twitter has become widespread among the Spanish universities since five years ago. The 97.4 per cent of them have got an institutional profile in this social network, whose most prominent properties are the brevity of their messages and the easiness to access to the information for all the users. This study demonstrates that the use of Twitter by the Spanish universities shows some clear characteristics: messages orientated to the students, contents connected with educational and cultural activities and lack of information about university research.